Sugammadex-associated asystole in young obese patient: Case report - Steven J. Lohmeier; David B. Powers (Oral and Maxillofacial Surgery Cases, 2022)
Sugammadex is a neuromuscular blocking (NMB) reversal agent that has quickly become popular among anesthesia providers since its FDA approval in 2015 due to its favorable properties. There are rare but significant and increasingly reported adverse cardiac events, including symptomatic bradycardia, asystole, cardiac arrest, and death. Since its introduction into the United States (US) market, there have been ten reported cases of asystole and cardiac arrest within minutes of sugammadex administration. Some incidents required cardiopulmonary resuscitation (CPR) and prolonged treatment in the Intensive Care Unit (ICU) for successful management. We present the youngest known case of sugammadex-associated asystole in a non-cardiac patient. Further investigation is warranted to understand better both the patient-related factors and drug administration techniques involved in Sugammadex-associated cardiovascular compromise to improve clinical decision-making for anesthesia providers.